Phytochemicals of Vitis vinifera L. var. King Ruby protect mice from benzo(a)pyrene-induced lung injury - Gehad S. Ahmedy; Hend M. Selim; Mona El-Aasr; Souzan M. Ibrahim; Suzy A. El-Sherbeni (Scientific Reports)
Abstract The world’s concern about smoking hazards, chronic obstructive pulmonary disease (COPD) and lung cancer was the motivation to investigate plants as a source of new drugs with lung protective effect. The phytochemical profile of Vitis vinifera L. var. King Ruby leaves methanol extract (VLME) was tentatively recognized by liquid chromatography electrospray ionization tandem mass spectrometric (LC-ESI-MS/MS). Fifty-two and forty-seven compounds were identified by negative and positive ESI modes, respectively. Taraxerol (1), β-sitosterol (2), daucosterol (3), quercetin-3-O-β-D-glucuronoide-6″-methyl ester (4) and isoquercetin (5) were isolated from VLME. The sulforhodamine B (SRB) assay of the different fractions against A-549 cell line revealed that the methylene chloride fraction (MCF) had the lowest cell viability at 300 µg/mL (4.54 ± 0.19%). Mice of 10 groups (n = 6) was treated as follows: Group I (negative control group), group II (disease control, mice received B(a)P 125 mg/kg, orally), groups III-V (mice received 100, 200, and 300 mg/kg of VLME, followed by B(a)P), group VI (mice received only 300 mg/kg of VLME), groups VII-XI (mice received 100, 200, and 300 mg/kg of MCF, followed by B(a)P), group X (mice received only 300 mg/kg of MCF). On the seventh day, all groups received a single oral dose of B(a)P 125 mg/kg body, except group I, VI and X. In vivo studies showed VLME and MCF (300 mg/kg body weight) effectively mitigated benzo(a)pyrene-induced lung injuries in mice. The anti-inflammatory effects were confirmed by the downregulation of cyclooxygenase-2 (COX-2) and CD34, alongside reduced nuclear factor-kappa B (NF-κB) expression. Antioxidant activity was indicated by decreased malondialdehyde (MDA) levels and inducible nitric oxide synthase (iNOS) expression with the remarkable increase in glutathione (GSH). Histological improvements further support the potential of Vitis vinifera L. leaves as a natural lung protectant. Further pre-clinical and clinical investigations will be required to deliver a new drug with promising protection effect.